Simulation Model to Assess Tidal Potential Energy in East Coast of Malaysia by using GIS - L. Y., Tan; Shahrani, Anuar; Ahmmad Shukrie, Md Yudin; F., Basrawi; Azim, Arshad (2014)
This article studies the GIS simulation of yearly power generation in five different tidal stations in the East Coast region of Malaysia. The tidal stations are Geting, Tanjung Gelang, Tioman, Tanjung Sedili and Cendering. The tidal station in Geting is not analysed in this study because the tidal range is insignificant. After analysing the lagoons nearby to the four tidal stations, Tanjung Gelang and Tanjung Sedili are chosen in this study based on their natural characteristics and geomorphology of lagoons. The simulation model is based on yearly power generation using tidal barrage. This article also looks into the model in term of mapping using GIS software to obtain bathymetry and tidal range data.